(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The aim of the study was to evaluate and compare the effect of growth promoter ’Megavit-DB’ on growth performance of indigenous Red Chittagong (RC) and Holstein Crossbred (HC) bull calves. For this purpose, six RC and six HC bull calves were assigned into four treatment groups having three calves in each as RCT0 (RC without Megavit-DB), RCT1 (RC with Megavit-DB), HCT0 (HC without Megavit-DB) and HCT1 (HC with Megavit-DB). The daily DM intake of different treatment groups were found almost similar. The daily average live weight gains were 0.27±0.05, 0.36±0.01, 0.36±0.01 and 0.45±0.05 kg/d, feed conversion efficiency were 9.08±0.16, 7.47±1.07, 7.13±1.24 and 6.16±0.27 and the average net returns (Tk.) were 1473.33±87, 2060±76.38, 1910±86.60 and 2776.67±44.10 for RCT0, RCT1, HCT0 and HCT1 treatment groups, respectively. The daily average live weight gain and feed conversion efficiency were significantly (p<0.05) higher in HCT1 than that from RCT1, HCT0 and RCT0. Accordingly, the average net returns were found significantly (p<0.05) higher in HCT1 than RCT1, HCT0 and RCT0. It may be concluded that Megavit-DB may have the potentials to improve growth performance of both HC and RC and may be used in cattle fattening program. Keywords: Growth performance; Red Chittagong; Holstein Crossbred; Megavit-DB DOI: 10.3329/jbau.v8i1.6403 J. Bangladesh Agril. Univ. 8(1): 83-86, 2010